(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This paper explores the transformative potential of modern technologies and interactive methodologies in the field of graphic drawing education. Traditional methods often struggle to engage learners effectively and cater to diverse learning styles. This study investigates how the integration of digital tools, software, and interactive teaching approaches can enhance student engagement, improve learning outcomes, and develop essential skills for the modern design landscape. Through a comprehensive review of literature and case studies, we analyze the benefits and challenges associated with implementing these advancements, highlighting best practices for educators seeking to revolutionize their graphic drawing curricula.